Women, Church, and Power: A Historical Study of Chuch Devaluation and Gender Inequality (Global Journal of Human-Social Science, 2025)
Due to the broad scope of the study of the feminine universe this article seeks to limit itself to reviewing the influence that Christianity received in the face of crises that during its expansion into different regions caused the modification of adoption of practices related to the role of women that were not the empowering and liberating practices initiated by Christ To this end the study realizes a bibliographic review and an analysis of various biblical texts and their interpretations in an attempt to understand the aspects of inequality between men and women The topic is articulated by presenting a review of the teachings and practices of Christ and the apostolic age Then it proceeds by briefly describing the following centuries up to the present day examining how the mixture of different cultures and interests both internal and external to the Church produced syncretism hybridization or religious inculturation within Christianity in its diversity This situation leaded to the devaluation of women within the ecclesiastical sphere due to issues of power The study concludes that the history of ecclesiastical devaluation of women has occurred due to syncretism between the Christian religion and its environment and due to internal power issues stemming from difficulties or biases in the interpretation of the biblical text This situation has not yet been fully resolved in the 21st century There are still challenges for theological and ecclesiastical studies to improve the status of women
Keywords: status of women Keywords: christianity history; biblical interpretation; women; leadership; gender inequality; early church